ANALISIS PEMBERLAKUAN UNDANG-UNDANG NOMOR 1 TAHUN 2022 PADA PAJAK BARANG DAN JASA TERTENTU PAJAK JASA PERHOTELAN DI BAPPENDA KOTA CIMAHI - Suresti Pratiningsih; Eko Setyanto (Yayasan Pendidikan Literasi Borneo, 2025)
The regional government is responsible for overseeing and managing its own administrative tasks based on the principles of independence and collaborative efforts. To ensure the effective and efficient distribution of state resources, it is important to establish guidelines on how the financial relationship between the central government and regional governments is managed fairly, balanced, and responsibly, while adhering to Pancasila and the 1945 Constitution of the Republic of Indonesia. The research approach used in this investigation involves descriptive techniques, utilizing a qualitative perspective. Data collection techniques used include library research, field research, and interviews. Then, the informants in this study were 6 people, who were determined purposively. The data analysis was carried out through triangulation. The results of the study concluded that the Potential Realization of Certain Goods and Services Tax Revenue and Hotel Tax in Cimahi City in the next 5 years will experience a significant increase.